2015
DOI: 10.1016/j.drugalcdep.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Group 1 mGlu-family proteins promote neuroadaptation to ethanol and withdrawal-associated hippocampal damage

Abstract: Background Group 1 mGlu-family proteins (i.e., mGlu) consist of mGlu1 and mGlu5 and their activity may influence voluntary ethanol intake. The present studies sought to examine the influence of these receptors on the development of ethanol dependence using in vitro and in vivo models of chronic, intermittent ethanol (CIE). Methods Rat hippocampal explants were exposed to CIE with or without the addition of mGlu1 antagonist (7-hydroxyimino)cyclopropa[b]chromen-1a-carboxylate ethyl ester (CPCCOEt; 0.5, 1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Heavy ethanol exposure impairs both spatial hippocampal-dependent memory and hippocampal long-term potentiation (LTP) in adolescent rats (Fernandes et al, 2018; Tapia-Rojas et al, 2018). Multiple hypotheses have been proposed to explain the ethanol-induced impairment in hippocampal synaptic plasticity, including glutamate and N-methyl-D-aspartate (NMDA) receptor dysfunction (Sabeti and Gruol, 2008), lower BDNF levels (Fernandes et al, 2018), decreased neurogenesis (Liu and Crews, 2017), increased cytokine levels (Cippitelli et al, 2017), DNA double-strand break (Suman et al, 2016) and mGlu1 receptor alterations (Reynolds et al, 2015), among others. Nevertheless, the effect of ethanol treatment in the interaction between astrocytes and neurons has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy ethanol exposure impairs both spatial hippocampal-dependent memory and hippocampal long-term potentiation (LTP) in adolescent rats (Fernandes et al, 2018; Tapia-Rojas et al, 2018). Multiple hypotheses have been proposed to explain the ethanol-induced impairment in hippocampal synaptic plasticity, including glutamate and N-methyl-D-aspartate (NMDA) receptor dysfunction (Sabeti and Gruol, 2008), lower BDNF levels (Fernandes et al, 2018), decreased neurogenesis (Liu and Crews, 2017), increased cytokine levels (Cippitelli et al, 2017), DNA double-strand break (Suman et al, 2016) and mGlu1 receptor alterations (Reynolds et al, 2015), among others. Nevertheless, the effect of ethanol treatment in the interaction between astrocytes and neurons has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…To date, few preclinical studies have investigated the effect of chronic alcohol administration on mGlu5 density, revealing either a mGlu5 hypoexpression in the hippocampus (6), an overexpression in the amygdala (7), or no alterations (8) or overexpression (9) in the ventral striatum. In contrast, extensive research showed that blocking of mGlu5 signaling by genetic or pharmacologic interventions reduces alcohol-rewarding properties (10)(11)(12)(13)(14) and the severity of withdrawal and relapse behaviors after alcohol deprivation in rodents (13,(15)(16)(17)(18)(19).…”
mentioning
confidence: 97%
“…The present study used an in vitro model of CIE that has been published previously (Reynolds et al, 2015A; Reynolds et al, 2015B) to delineate the influence of intracellular CA 2+ from ER-bound receptors in promoting withdrawal-associated loss of hippocampal NeuN/Fox-3. In brief, male and female rat hippocampal explants were randomly transferred at 5 days in vitro to plates containing either 1 ml of the ethanol-naïve culture media (control) or ethanol-containing media (i.e., 0 and 50 mM) for five days with or without the addition of xestospongin C (0.5 μM), a membrane-permeant inhibitor of IP3-mediated CA 2+ release or BD-1047 (20 and 80 μM), a selective antagonist at the σ−1 receptor (Kim et al, 2010; Taylor & Tovey, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…This treatment regimen was repeated a total of three times. Xestospongin C was first dissolved in 100% dimethyl sulfoxide (DMSO; Fisher) to yield a final working concentration of 0.01% DMSO in the ethanol-naïve and ethanol-containing culture media (after Reynolds et al, 2015B). Concentrations of xestospongin C (i.e., 0–0.5 μM) and BD-1047 (i.e., 0–80 μM) were selected based on prior reports showing efficacy in reducing withdrawal-associated neurotoxicity from other drugs of abuse, such as methamphetamine when applied acutely (Smith et al, 2008; Smith et al, 2010).…”
Section: Methodsmentioning
confidence: 99%